Juventudes na cidade: um estudo sobre formação e participação - Siqueira, Lee Osvaldi Alves (2014)
Youth as a concept and youths as manifestations of several realities are historically treated and situated. The relationship between education and participation of young people in the construction of policies was the focus of this research, which issued the formation as it is presented nowadays: if these people are not able to be built as a constructor of autonomy, we questioned ourselves on what can be reached by these youths? Are they being educated for what kind of participation? How do they assume culture in search of autonomy and emancipation, even though they are still inside the parameters of the capitalist world? The initial hypotheses showed some indifference from the youth in participating of social issues, maybe a difficulty of the society in opening spaces for the youths participation and also the absence of an education that enables a democratic participation. The research tried to analyze the process of construction and effectiveness of a social movement, with the aim of mapping the youths from Mogi das Cruzes. Furthermore, to assess the relationships that are established in the action of being the main role in the construction of a public policy that brings in its competence questions concerning the problematic presented, observing what progresses and what is kept regressed between the youth and social interest. As the theoretical reference, the critical theory of Frankfurt s school, mainly Adorno, was used. The community study method of empiric social investigation included valuable inquiry about the construction of these youths mapping. As the result of such analyses, although there is some difficulty of young people in realizing the importance of their participation, it was found that the methodologies and techniques used could be important to cause such attitude in them, if they met their interests. Young people are submitted to pseudo-education, which is intimately connected to the reproduction of the capital logics in a managed culture, even though there is still great wealthy in the diversity of rural and urban territories that can be considered and best comprehended. The social movement that was investigated enabled to understand that communities where there is opening for youth, the actuation becomes more intense, and where there are educational institutions (formal and non-formal ones) that assume the condition of communities representatives, there is a strong interference of ideologies of the institutions that they represent.